Bridge of civilizations : the Near East and Europe, c. 1100-1300 - Edbury, P. W.; Pringle, Denys,; Major, Balázs, (Archaeopress Publishing Ltd, 2019)
This volume considers the links and contrasts between Europe and the areas around the eastern Mediterranean that were visited and occupied by western crusaders and settlers in the twelfth and thirteenth centuries, giving special attention to the evidence provided by archaeology and material culture, as well as historical sources.